Electrocatalysis of Cu−MOF/Graphene Composite and its Sensing Application for Electrochemical Simultaneous Determination of Dopamine and Paracetamol. Issue 6 (19th February 2019) - Ma, Baolong; Guo, Hao; Wang, Mingyue; Li, Li; Jia, Xueyan; Chen, Huiqin; Xue, Rui; Yang, Wu
Abstract: A nanocomposite of HKUST‐1 (MOF) and electroreduction graphene oxide (ERGO) is prepared and applied as an electrochemical sensor for the simultaneous determination of paracetamol and dopamine by means of one‐step electrodeposition. The MOF/ERGO composite displays excellent electrochemical catalytic activities towards the paracetamol and dopamine, which is attributed to the synergistic effect of big surface area, porosity and high electrocataytic activity of the MOF and good conductivity of ERGO. The modified electrode could be applied to determine simultaneously paracetamol and dopamine in biochemical samples with wide linear ranges (0.2 μM to 160 μM for paracetamol and 0.2 μM to 300 μM for dopamine) and low detection limits (0.016 μM for paracetamol and 0.013 μM for dopamine). Meanwhile, the proposed sensor still displays high sensitivity, good selectivity and excellent stability. Abstract :